A comparative study in the outcome between the two fixed doses of polyvalent anti snake venom, 10 vials versus 20 vials, with mechanical ventilation in children with severe neurotoxic snake envenomation - V., Shekar; Soren, Chapay; Reddy, K. Venkataramana; V. V., Lakshmi Aparnadevi; Kumar, Sai (International Journal of Contemporary Pediatrics, 2020)
Background: Every year about 50,000, people die of snake bites in India. Anti-snake venom and mechanical ventilation is mainstay of treatment in cases with severe neurotoxic envenomation. ASV is costly and scarce resource. There is lack of universal consensus towards the optimal dose of ASV in management protocol for children with severe neurotoxic snake envenomation. Objective was to compare the difference in outcome between two fixed doses of ASV, 10vials versus 20 vials, in children with severe neurotoxic snake envenomation Methods: This comparative observational study was carried out for a period of 3 years in Department of Pediatrics of SVS Medical College, Mahabubnagar, Telangana, India. Children with history of snake bite and clinical evidence of neuroparalysis were included. In addition to the mechanical ventilation and other supportive measures, every alternate patient was administered with 10vials (low dose) and 20 vials (high dose) of ASV over 1 hour. Outcome was compared between the two groups. Results: Of the 62 patients, 32 were in each group. The median time to extubation was 41 hours and 39.5 hours and mean duration of the hospital stay was 4.6 days and 4.5 days among the low dose and high dose groups, respectively. There were three deaths, one from low dose group and two from high dose group. Conclusions: There was no significant difference in outcome between the 10 vials vs 20 vials of ASV in addition to mechanical ventilation in treatment of children with severe neurotoxic snake envenomation. So, 10 vials of ASV can be utilized to reduce the cost of treatment.